Wacana komunikasi dalam al-Quran: satu analisis terhadap dialog dua hala - Mohd Abdul Nasir Abd. Latif (Tanjong Malim, 2014)
Wacana komunikasi dalam al-Quran: satu analisis terhadap dialog dua hala by Mohd Abdul Nasir Abd. Latif